2021
DOI: 10.1149/2162-8777/ac1d61
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Titanium Substrate Effect on the Morphology of Anodic TiO2 Nanotubes

Abstract: We report the synthesis of novel titanium dioxide nanotube arrays (TNAs) via an anodization process using five different kinds of titanium foils as working electrodes. This reveals that the morphology of TNAs in impacted by the purity, conductivity, and mechanical properties of the titanium sheets. Under the same electrochemical conditions, when titanium foil with purity of 99.7% was used as the working electrode, the TNAs with maximum aspect ratio was obtained compared to that prepared by low purity metal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The morphology of the as-annealed secondary oxidized TiO 2 nanotube (TiO 2 NT) is shown in Figure S1 . Typically, a regular network structure is formed on the top of the TiO 2 nanotube, resulting in its large specific surface area [ 25 ]. The top of the TiO 2 NT array has a double-layer honeycomb structure, which is conducive to photocatalysis and energy storage [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphology of the as-annealed secondary oxidized TiO 2 nanotube (TiO 2 NT) is shown in Figure S1 . Typically, a regular network structure is formed on the top of the TiO 2 nanotube, resulting in its large specific surface area [ 25 ]. The top of the TiO 2 NT array has a double-layer honeycomb structure, which is conducive to photocatalysis and energy storage [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Typically, a regular network structure is formed on the top of the TiO 2 nanotube, resulting in its large specific surface area [ 25 ]. The top of the TiO 2 NT array has a double-layer honeycomb structure, which is conducive to photocatalysis and energy storage [ 25 , 26 , 27 ]. Therefore, we use the secondary oxidized TiO 2 nanotube (TiO 2 NT) as a matrix to prepare high-performance catalyst and lithium battery anode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 By exploring the changes of the TNTs morphology of titanium sheets with different purities after anodization, Zhang et al showed that titanium dioxide nanotubes are closely related to the purity, electrical conductivity, and mechanical properties of titanium sheets. 15 From these, we can see the improvement effect of TNTs ordered morphology for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 86%
“…It is concluded that the anodizing voltage has a significant effect on the morphology, structure, photoelectrochemical properties, and hydrogen production of nanometer titanium dioxide, while Cao et al explored the effects of different F-ion concentrations and anodizing times on the morphology of nanotubes and evaluated the battery performance . By exploring the changes of the TNTs morphology of titanium sheets with different purities after anodization, Zhang et al showed that titanium dioxide nanotubes are closely related to the purity, electrical conductivity, and mechanical properties of titanium sheets . From these, we can see the improvement effect of TNTs ordered morphology for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%